Celebrating Virtual Existence on Social Class and Social Media - Dwi Prasetyo; Tia Saraswati; Mochammad Arkansyah (LPPM Stikosa - AWS, 2023)
This research involves a qualitative descriptive method in which the researcher describes different situations, conditions, and variables. To collect relevant data, the research utilizes secondary data techniques and photo searches on social media. Flexing, which has become a new and popular culture among the public, has become a widely discussed issue across various social groups. Flexing content on social media platforms like Instagram, TikTok, and Facebook is often posted with the intention of gaining recognition, honor, and social status, although the wealth displayed may not always come from personal asset ownership.